Cloning and functional analysis of the root‐knot nematode resistance gene NtRk1 in tobacco. Issue 2 (29th March 2023) - Zhang, Luyang; Xu, Zhiqiang; Jiang, Zhimin; Chen, Xiaoxiang; Li, Bo; Xu, Liping; Zhang, Zhiqiang
Abstract: Tobacco ( Nicotiana tabacum L.) is an economically important crop worldwide. Root‐knot nematodes (RKNs) are responsible for yield losses in tobacco and other crops, such as tomato, potato, peanut, and soybean. Therefore, screening for resistance genes that can prevent RKN infestation and the associated damage is crucial. However, there is no report of cloning tobacco RKN resistance genes to date. Here, we cloned the tobacco RKN resistance gene NtRk1 from the resistant variety TI706, using rapid amplification of cDNA ends. NtRk1 has high homology with other RKN resistance genes ( CaMi in pepper, Mi‐1.1 and Mi‐1.2 in tomato). Under normal conditions, NtRk1 was barely expressed in the roots; however, following RKN infection, its expression level rapidly increased. Overexpression of NtRk1 in the susceptible cultivar "Changbohuang" enhanced its resistance to Meloidogyne incognita, while RNA interference of NtRk1 in the resistant cultivar K326 resulted in its susceptibility to M. incognita . Moreover, compared with resistant variety K326, we found the salicylic acid and jasmonic acid contents of RNAi plants decreased after inoculation with M. incognita, and confirmed that the function of NtRk1 is related to these phytohormones. These findings indicate that NtRk1 is an RKN resistance gene, which is abundantly expressed in response to RKN infection and may enhance host defense responses by elevating salicylic acid and jasmonic acid levels.